Graphical visualization principles for maintaining functional relativity of spaces during architectural design - Hoseini, Ali Ghaffarian; Ibrahim, Rahinah; Abdullah, Rusli (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
Maintaining the functional relativity of spaces during architectural conceptual design phase is difficult when performed manually specifically while facing a huge amount of complicated relativity of spaces in more complex buildings. This paper presents a proof-of-concept model using an available Social Network Analysis (SNA) tool to facilitate spatial diagramming visualization during conceptual design phase. Utilization of SNA was examined at four incremental levels. The initial level determined the feasibility of our research while the second level focused on prioritizing values for the spaces and the relations between the spaces. The third level examined the classification possibility of architectural spatial relationships in one horizontal plan. The fourth level examined if we could develop multiple layers that are connected by one common connector. We intellectually validated our research by comparing our model with another manual diagram by Nooshin (2001). We expect our study to provide us guidelines in developing prototype for a spatial diagramming tool using SNA, which architects can use to maintain the functional relativity of spaces through a pre-defined matrix.